Hubungan Asupan Protein dengan Kecukupan ASI pada Pasien Post Operasi Sectio Caesaria Di Rumah Sakit Umum Pringsewu - Desi Ari Madi Yanti (LPPM Sikes Panca Bhakti Bandar Lampung, 2019)
The nutrition sufficiency is not only needed by the baby but also nutrition necessity will increase especially toward puerperium mother with Secsio sesaria surgical post. The nutrition is needed for decrease the injury, decrease infection suspectible then mother’s milk sufficiency for the baby. As known the relation of protein with mother’s milk to the Post Op Sectio Caesarea (SC) in Pringsewu hospital. This research is using analytic method with cross sectiona approach. The population in this research is post op SC mother in Pringsewu hospital with 45 respondents who fulfil inclusive criteria. Sampling technique is using Purposive Sampling. Data analyze is using cgi square statisticts with sense level<0.05. The result of bivariat analyze shows there is the relation of protein consumption with mother’s milk suffciency to post op SC patient with p = 0.035 whereas p<0.05. This research is recomendate to family does not do eating prohibition especially protein that comes from animal for post op SC mother.